The Influence of Competition, Financing Risk, and Capital Adequacy on the Stability of Islamic Commercial Banks in Indonesia - Umiyati; Widiyawati, Iin (LPPM ISNJ Bengkalis, 2025)
This study aims to analyze the influence of competition, financing risk, and capital adequacy on the stability of Islamic commercial banks in Indonesia. The research used panel data regression methods on 10 Islamic commercial banks in Indonesia from 2019–2023. The Z-Score approach was employed to measure bank stability. The results show that financing risk and capital adequacy significantly affect bank stability, while competition does not have a significant effect. Simultaneously, all three variables significantly influence stability. The findings emphasize the importance of improving risk management and capital reserves in maintaining financial stability amid increasing competition in the Islamic banking sector.